A checklist of the genus Tomosvaryella Aczél (Diptera: Pipunculidae) from the Middle East with the description of a new species. Issue 4 (2nd October 2017) - Majnon Jahromi, Bahareh; Gheibi, Mehdi; Fallahzadeh, Majid; Kehlmaier, Christian; Hesami, Shahram
Abstract : A checklist of 39 species of the genus Tomosvaryella Aczél (Diptera, Pipunculidae) known from the Middle East is provided. A new species, T. hamata Majnon Jahromi & Kehlmaier sp. n. is described from southern Iran and diagnostic characters of male and female terminalia are illustrated. Tomosvaryella dentiterebra (Collin, 1949 ) is redescribed and male and female terminalia are illustrated for the first time. A phylogenetic maximum-likelihood analysis and uncorrected pairwise genetic distances of 18 out of 22 Iranian species of Tomosvaryella based on DNA barcodes of the mitochondrial COI gene are presented and also discussed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:FF8C116D-0C92-431A-B52C-11F3711B6A62